Child Adjustment and Parent Efficacy scale-Development Disability (CAPES-DD) : First psychometric evaluation of a new child and parenting assessment tool for children with a developmental diability - Emser, T.; Mazzucchelli, Trevor; Christiansen, H.; Sanders, M. (Pergamon Press, 2016)
This study examined the psychometric properties of the Child Adjustment and Parent Efficacy Scale-Developmental Disability (CAPES-DD), a brief inventory for assessing emotional and behavioral problems of children with developmental disabilities aged 2- to 16-years, as well as caregivers' self-efficacy in managing these problems. A sample of 636 parents participated in the study. Children's ages ranged from 2 to 15. Exploratory and confirmatory factor analyses supported a 21-item, three-factor model of CAPES-DD child adjustment with 13 items describing behavioral (10 items) and emotional (3 items) problems and 8 items describing prosocial behavior. Three additional items were included due to their clinical usefulness and contributed to a Total Problem Score. Factor analyses also supported a 16-item, one factor model of CAPES-DD self-efficacy. Psychometric evaluation of the CAPES-DD revealed scales had satisfactory to very good internal consistency, as well as very good convergent and predictive validity. The instrument is to be in the public domain and free for practitioners and researchers to use. Potential uses of the measure and implications for future validation studies are discussed.